Bibliometric Analysis of Private Credit - Loso Judijanto (West Science Social and Humanities Studies, 2025)
This study conducts a bibliometric analysis of private credit research to examine its intellectual structure and thematic evolution. By analyzing scholarly publications indexed in the Scopus database, the study maps the development of private credit research over time, identifying key authors, institutions, and thematic clusters. The results reveal the growing prominence of sustainability, climate change, and environmental finance in recent private credit research, highlighting the role of non-bank financial institutions in providing tailored financing solutions. The analysis also uncovers traditional themes such as credit systems, monetary policies, and banking competition, while highlighting the emerging focus on blockchain technology and algorithmic transparency in credit risk management. This study provides valuable insights for policymakers, financial institutions, and researchers, offering guidance on future research directions and the integration of private credit within broader economic and social frameworks.